The Influence of Perceived Value Dimensions on Customer Satisfaction in Using Garmin Smartwatches - Steffania Alodia; Kristiningsih (International Conference on Economics, Management, Business, and Accounting, 2024)
The rapid development of technology makes human life easier and simpler. One example of technological development is the emergence of wearable technology such as smartwatches. This research was conducted to determine the influence of perceived value dimensions on customer satisfaction in using Garmin smartwatches. The number of samples used in this research was 50 respondents. The sampling technique used in this research is non-probability sampling with a purposive sampling method. The results of this research state that emotional value has a significant effect on customer satisfaction. Meanwhile, performance value, price value, and social value do not have a significant effect on customer satisfaction. The implications of this research are useful for companies to implement strategies to create customer satisfaction.